Tectonic and Climatic Control on Quaternary Exhumation in the Eastern Pamir Domes, Western China: Insights From Geomorphic Approaches - Cao, Kai; Mai, Hongtao; Chevalier, Marie-Luce; Wang, Guocan (Frontiers in Earth Science, 2022)
The Kongur Shan and Muztaghata massifs, bounded by the Kongur Shan extensional system (KES), represent tectonic and topographic anomalies in the eastern Pamir region. They are ideal examples to study how normal faulting and surface erosion influence Quaternary exhumation/erosion of the dome system. We apply multiple geomorphic parameters, including hypsometric integral, stream length-gradient index, drainage basin shape, drainage basin asymmetry and ratio of valley floor width to valley height, for the catchments on both sides of the range. We first evaluated the validity of various indices and chose three active tectonic-sensitive indices to establish a newly-integrated parameter (Iat) that is used to measure relative intensities of tectonic activity in active orogens. Results suggest stronger tectonic activity west of the domes along the Kongur Shan normal fault (KSF) and Muji dextral strike-slip fault, compared to the eastern side, along the Ghez and Kalagile faults. This first-order observation reflects tectonic control on the topographic development of the domal structure, consistent with eastward crustal tilting, attested by older thermochronology ages to the east. On the western flank of the range, stronger tectonic activity occurs mostly on the Muji fault, Kingata Tagh - Kongur Shan fault segment, as well as along the western and southern Muztaghata segments of the KSF. This is consistent with field investigations of Quaternary offsets of landforms, which suggest continuous activity of the Muji fault and KSF since the late Miocene. Average basin-wide erosion rates derived from stream power models are highest near the Kongur Shan dome, and gradually decrease southwards and northwards, in agreement with the spatial pattern of long-term exhumation rates in the footwall of the KSF obtained by low-temperature thermochronology data. Positive correlation between exhumation/erosion rates and extensional rates along the active faults located west of the domes indicates that extensional deformation likely plays a dominant role in controlling focused dome exhumation/erosion. However, considering peaked exhumation/erosion rates, stronger rock resistivity and steeper glacial landforms, attest to the important role of glacial buzz-saw in reshaping the recent dome’s landscape.